PENGARUH KOMPENSASI TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA PT. HONDA WILTOP AUTO JAMBI - Sari, Liza Amelia; Rosita, Sry; Hasanah, Nur (Jurnal Dinamika Manajemen, 2018)
This research aims to know the compensation influence on employees' organizational commitment. This study involved 58 respondents who are employees of PT. Honda Wiltop Auto Jambi. A detailed questionnaire has used as a data collection method, while the analysis method used simple linear regression. The result showed which compensation has a significant positive effect on organizational commitment. The value of the t causes it is significantly larger than the t quantification, the variable compensation of 0.553 regression, which means that the better system of awarding prizes will increase the organization's commitment by 0.553. The resulting value of R square on 0.363 means that contribution of compensation on 36.43% informing organizational commitment variable, and forming the rest by the outside variable of this study.